Handbook of emergency response to toxic chemical releases : a guide to compliance - Cheremisinoff, Nicholas P. (Noyes Publications, 1995)
This handbook has been prepared as a working reference for the safety officer, the environmental engineer and the consultant. For the safety officer, this handbook provides guidelines and instructions in preparing Right-to-Know Reporting Audits, establishing programs and training employees on hazard awareness, and developing and implementing emergency response programs in the workplace and at off-site operations. For the environmental engineer, this handbook provides technical data on toxic chemical properties and an instructional aid on how to properly prepare toxic chemical release inventory reporting.
Includes index.
Keywords: Hazardous substances -- Safety measures -- Handbooks, manuals, etc.; Hazardous substances -- Accidents -- Handbooks, manuals, etc.; Chemical spills -- Reporting -- Handbooks, manuals, etc.; elektronické knihy; electronic books